Computer Developments in the Soviet Union - Murphy, Mary E. (Academy of Management Journal, 1960)
Reports on the computer development project and decentralization program adopted by the Union of Soviet Socialist Republic during the 1950s. Evaluation of machineries used by manufacturing industries; Assessment of industrial productivity in utilizing automatic production lines; Government policies on technological innovation.